The spectra of Uranus and Neptune at 8-14 and 17-23 μm - Orton, G; Aitken, D; Smith, C; Roche, P; Caldwell, J; Snyder, R (1987)
An array spectrometer was used on the nights of 1985 May 30-June 1 to observe the disks of Uranus and Neptune in the spectral regions 7-14 and 17-23 μm with effective resolution elements ranging from 0.23 to 0.87 μm. In the long-wavelength region, the spectra are relatively smooth with the broad S(1) H2 collision-induced rotation line showing strong emission for Neptune. In the short-wavelength spectrum of Uranus, an emission feature attributable to C2H2 with a maximum stratospheric mixing ratio of 9 × 10-9 is apparent. An upper limit of 2 × 10-8 is placed on the maximum stratospheric mixing ratio of C2H6. The spectrum of Uranus is otherwise smooth and quantitatively consistent with the opacity provided by H2 collision-induced absorption and spectrally continuous stratospheric emission, as would be produced by aerosols. Upper limits to detecting the planet near 8 μm indicate a CH4 stratospheric mixing ratio of 1 × 10-5 or less, below a value consistent with saturation equilibrium at the temperature minimum. In the short-wavelength spectrum of Neptune, strong emission features of CH4 and C2H6 are evident and are consistent with local saturation equilibrium with maximum stratospheric mixing ratios of 0.02 and 6 × 10-6, respectively. Emission at 8-10 μm is most consistent with a [CH3D]/[CH4] volume abundance ratio of 5 × 10-5. The spectrum of Neptune near 13.5 μm is consistent with emission by stratospheric C2H2 in local saturation equilibrium and a maximum mixing ratio of 9 × 10-7. Radiance detected near 10.5 μm could be attributed to stratospheric C2H4 emission for a maximum mixing ratio of approximately 3 × 10-9. Quantitative results are considered preliminary, as some absolute radiance differences are noted with respect to earlier observations with discrete filters. © 1987.